PENGERTIAN DAN RUANG LINGKUP TAFSIR TARBAWI - Abdul Wahab Syakhrani; Novia Fitri Rahmatina; Siti Radhina; Siti Rahmah; Sri Kamaliah; Zahratunnisa (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Tafsir Tarbawi is a discipline that studies and explains verses from the Qur'an from an educational perspective. This approach emphasises character building, morality, and personal development in line with the values of the Qur'an. Tarbawi interpretation aims to guide individuals to understand and apply the educational messages of the Qur'an in their daily lives, thereby strengthening leadership, social awareness, and social benefits in a broad sense. The scope of tafsir tarbawi covers educators, Islamic educational materials, delivery methods, and the application of Qur'anic verses in the context of education and civilisation development in accordance with the guidance of the Qur'an. This approach to interpretation includes thematic and maudhu'i analysis methods that focus on exploring explicit and implicit educational messages in the Qur'an to be applied in the world of Islamic education, particularly in formal and non-formal educational institutions. Thus, tarbawi interpretation is an interpretation of the Qur'an that serves as a conceptual and methodological foundation in Islamic education studies, which aims to shape students with comprehensive and applicable Islamic values.